Study of Information and Communication Technology Effect on Entrepreneurship in small and Medium Enterprises (Survey on Small and Medium Enterprises of Semnan Industrial Park) - davood Feiz; Zarei Zarei; Karimi Karimi (Journal of Information Technology Management)
In order to gain benefits from entrepreneurship in small and medium enterprises (SMEs), it is necessary to concentrate on and invest in effective factors on entrepreneurship. One of these factors is paying attention to Superior technology. In spite of that, the studies have shown that most of SMEs don’t pay enough attention to the advantages that technology can offer. This article studies the effects of information and communication technology (ICT) on entrepreneurship in small and medium enterprises of Semnan industrial park. The study has a descriptive-survey format and has used questionnaire as a research tool to obtain data. The reliability of the research questionnaire is proved through a high value of Cronbach’s alpha coefficient (96.2). The results of one-sample T-test have demonstrated that ICT has no meaningful effect on emerging entrepreneurship and also new businesses, process innovativeness , risk taking, self-renewal and competitive aggressiveness of small and medium enterprises of Semnan industrial park, but has been effective on product/service innovativeness and proactiveness